The Effects Of Simvastatin On Islets Of Langerhans In The Pancreas Of Rats: A Histological And Biochemical Study - Qamar, Abdullah; Khan, Hammad Gul; Kundi, Hina; Ali, Ayesha; Bashir, Sumyyia; Khurshid, Tooba (Journal of Rawalpindi Medical College, 2024)
Objective: This study explored the effect of simvastatin on the histomorphology of islets of Langerhans, glucose and insulin levels in rats. Study Design: The study was a one-year laboratory-based experimental control trial. Place and duration of study: It was conducted at Army Medical College Rawalpindi, in collaboration with the National Institute of Health Islamabad and Armed Force Institute of Pathology Rawalpindi. Methods: A one-year, laboratory-based, two-group experimental control trial was conducted. Thirty rats were assigned to each group: a control group receiving saline injections, and a simvastatin group receiving a simvastatin 60 mg/kg/day. Histological analysis of pancreatic islets, and measurements of blood glucose and insulin levels were performed. Statistical analysis was conducted using independent sample t-tests, with significance set at p < 0.005. Results: While simvastatin treatment did not affect the number of islets of Langerhans, The area of pancreatic islets of Langerhans was significantly higher in the simvastatin treatment group compared to control (52,664±38,871 μm2 vs 24,643±16,256 μm2, p=0.001). Serum insulin levels were also significantly elevated with simvastatin treatment (21.49±7.03 μIU/ml) compared to control (16.72±5.38 μIU/ml) (p=0.005). There were no significant differences in weekly fasting blood glucose levels at 4 or 12 weeks between groups (p>0.05). These findings suggest potential modulation of pancreatic islet function by simvastatin without affecting glycemic control in this model. Conclusions: These findings demonstrate that simvastatin treatment significantly impacts the morphology and function of pancreatic islets in rats, increasing insulin secretion without affecting blood glucose levels. Further research is necessary to elucidate the underlying mechanisms and clinical implications of these observations. Keywords: Simvastatin, islets of Langerhans, Sprague-Dawley rats, insulin, glucose, pancreas.